A Simple Spectrophotometric Method for the Determination of Thiobarbituric Acid Reactive Substances in Fried Fast Foods - Zeb, Alam (Hindawi Publishing Corporation, 2016)
A simple and highly sensitive spectrophotometric method was developed for the determination of thiobarbituric acid reactive substances (TBARS) as a marker for lipid peroxidation in fried fast foods. The method uses the reaction of malondialdehyde (MDA) and TBA in the glacial acetic acid medium. The method was precise, sensitive, and highly reproducible for quantitative determination of TBARS. The precision of extractions and analytical procedure was very high as compared to the reported methods. The method was used to determine the TBARS contents in the fried fast foods such as Shami kebab, samosa, fried bread, and potato chips. Shami kebab, samosa, and potato chips have higher amount of TBARS in glacial acetic acid-water extraction system than their corresponding pure glacial acetic acid and vice versa in fried bread samples. The method can successfully be used for the determination of TBARS in other food matrices, especially in quality control of food industries.